Determinan Percepatan Penyembuhan Luka Perineum pada Ibu Nifas dengan Pemberian Konsumsi Ikan Gabus (Channa Striata) - Sri Susilawati; Meti Patimah; Melsa Sagita Imaniar (Faletehan Health Journal, 2020)
Perineum tears are obstetric tears that occur in the perineum area due to the inability of the muscles and soft tissues of the pelvic to accommodate the birth of the fetus. Perineum wounds that are not properly oversed can inhibit wound healing and result in infection. The level of consumption of nutritious foods affects wound healing in humans, one of which is by consuming snackhead fish (Channa Striata). The purpose of this study is to find out determinant of the acceleration of perineum wound healing in postpartum by giving consumption of snakehead fish (Channa Striata). The research method used is an analytical survey with a cross sectional approach that is a study to study the dynamics of correlation between risk factors and effects, by way of approach, observation or data collection at a time (point time approach), the large sample in this study is postpartum from the first day of childbirth as many as 30 people, sampling technique using Purposive Sampling technique, data collection method is by intervening specifically by giving snakehead fish one day 3x for 10 days, research instruments used in this study are operational standard procedure (SOP) perineum wound healing, data analysis using univariate analysis and bivariate analysis. The results of this study showed that the length of healing of maternal perineum wounds is in the category of <=7 days which is as much as 60%, while 40% is in the category of healing length >7 days. Age, parity, education, early mobilization, and types of wounds affect the length of healing of perineum wounds in the postpartum.